Knowledge, attitude, and practice of teledentistry in periodontal diagnosis: Is it the required upgrade to conventional periodontics? - Gautami Subhadra Penmetsa; B Bharghavi Patnaik; M V Ramesh; K S V. Ramesh; Keerthi Vinnakota; Sravanthi Vundavalli (Wolters Kluwer Medknow Publications, 2023)
Background: Teledentistry which is similar to telemedicine has emerged as a new tool for various dental disciplines. Teleperiodontics is a branch of telehealth which focuses on the application of digital communication technology into the field of periodontics without demanding a specialist presence. An early detection and diagnosis of periodontal conditions can not only treat the disease in its early stage but also prolong the health of the periodontium, thereby improving the overall quality of life of an individual. However, teledentistry has not penetrated into the field of periodontics to a level it has to in providing periodontal care. Hence, the aim of this questionnaire study was to assess the knowledge, attitude, and application of teleperiodontics into everyday practice among the dental surgeons at various levels. Materials and Methods: An electronic questionnaire consisting of 29 close-ended questions including sections assessing the knowledge, attitude, and practice of teledentistry and teleperiodontics was sent to dental colleges present in East and West Godavari districts of Andhra Pradesh. Results: A total of 350 responses were received and 80.57% dental surgeons were aware about teledentistry, and a total of 74% dental surgeons were likely to prescribe oral hygiene aids and medication for temporary management of periodontal conditions. Conclusion: Teleperiodontics is an emerging science whose knowledge, attitude, and application are yet to be explored.